2021
DOI: 10.2138/am-2020-7014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a new H2O-independent thermometer based on olivine-melt Ni partitioning at crustal pressure

Abstract: An olivine-melt thermometer based on the partitioning of Ni (DNiOl/liq) was hypothesized by Pu et al. (2017) to have a negligible dependence on dissolved water in the melt (and pressure variations from 0–1 GPa), in marked contrast to thermometers based on DMgOl/liq. In this study, 15 olivine-melt equilibrium experiments were conducted on a basaltic glass starting material (9.6 wt% MgO; 353 ppm Ni) to test this hypothesis by comparing the effect of dissolved H2O in the melt on DMgOl/liq and DNiOl/liq on the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…15; Table 4A). This result also shows internal consistency with application of the Ni thermometer of Pu et al (2017Pu et al ( , 2021. All the remaining samples fail the Mn-Mg K D (oliv-melt) test, with differences of >0.04 between analyzed values (this study; Table 4B) and those calculated from the model of Blundy et al (2020) and analyzed values (this study; Table 4B).…”
Section: Additional Test Of Olivine-melt Equilibrium At the Liquidussupporting
confidence: 76%
See 3 more Smart Citations
“…15; Table 4A). This result also shows internal consistency with application of the Ni thermometer of Pu et al (2017Pu et al ( , 2021. All the remaining samples fail the Mn-Mg K D (oliv-melt) test, with differences of >0.04 between analyzed values (this study; Table 4B) and those calculated from the model of Blundy et al (2020) and analyzed values (this study; Table 4B).…”
Section: Additional Test Of Olivine-melt Equilibrium At the Liquidussupporting
confidence: 76%
“…For example, Albert et al (2020) showed that the texture of olivine phenocrysts changes in a stratigraphic sequence of erupted tephra from a monogenetic cone, corresponding to variations in rapid ascent rates via fractures to the surface. However, there is no evidence that textural disequilibrium corresponds to chemical disequilibrium, as demonstrated by the olivine-melt equilibrium experiments conducted by Pu et al (2021). In that experimental study, samples held above the liquidus and then rapidly dropped below the liquidus and held for 8-24 h, grew large, sparse olivine crystals with diffusion-limited growth textures.…”
Section: Hypothesis 4: Disequilibrium Due To Kinetics Of Rapid Growthmentioning
confidence: 93%
See 2 more Smart Citations
“…Inferring the Fe 3+ /Fe 2+ ratios in the melt from the composition of silicate melt -olivine pairs require the accurate estimation of the value of , − ⁄ . The partitioning of Mg between olivine and melt was shown to be influenced by H 2 O (Putirka et al 2007;Pu et al 2017Pu et al , 2021, whereas the dissolved H 2 O content has been shown to have no significant effect on the ferric/ferrous ratio in silicate melts (Moore et al 1995;Gaillard et al 2001 concentration in the silicate melt based on the measured olivine compositions and the measured Mg concentrations in the melt. The concentration of Fe 3+ in the melt was obtained by calculating the difference between the measured total Fe in the melt and the estimated Fe 2+ concentration.…”
Section: Discussionmentioning
confidence: 96%